Defining the minimal important difference for the visual analogue scale assessing dyspnea in patients with malignant pleural effusions. - Mishra, E; Corcoran, J; Hallifax, R; Stradling, J; Maskell, N; Rahman, N (PLOS, 2015)
BACKGROUND: The minimal important difference (MID) is essential for interpreting the results of randomised controlled trials (RCTs). Despite a number of RCTs in patients with malignant pleural effusions (MPEs) which use the visual analogue scale for dyspnea (VASD) as an outcome measure, the MID has not been established. METHODS: Patients with suspected MPE undergoing a pleural procedure recorded their baseline VASD and their post-procedure VASD (24 hours after the pleural drainage), and in parallel assessed their breathlessness on a 7 point Likert scale. FINDINGS: The mean decrease in VASD in patients with a MPE reporting a 'small but just worthwhile decrease' in their dyspnea (i.e. equivalent to the MID) was 19mm (95% CI 14-24mm). The mean drainage volume required to produce a change in VASD of 19mm was 760ml. INTERPRETATION: The mean MID for the VASD in patients with a MPE undergoing a pleural procedure is 19mm (95% CI 14-24mm). Thus choosing an improvement of 19mm in the VASD would be justifiable in the design and analysis of future MPE studies.